G protein-coupled receptors in cochlea: Potential therapeutic targets for hearing loss - Ma, Xiangyu; Guo, Jiamin; Fu, Yaoyang; Shen, Cangsong; Jiang, Pei; Zhang, Yuan; Zhang, Lei; Yu, Yafeng; Fan, Jiangang; Chai, Renjie (Frontiers in Molecular Neuroscience, 2022)
The prevalence of hearing loss-related diseases caused by different factors is increasing worldwide year by year. Currently, however, the patient’s hearing loss has not been effectively improved. Therefore, there is an urgent need to adopt new treatment measures and treatment techniques to help improve the therapeutic effect of hearing loss. G protein-coupled receptors (GPCRs), as crucial cell surface receptors, can widely participate in different physiological and pathological processes, particularly play an essential role in many disease occurrences and be served as promising therapeutic targets. However, no specific drugs on the market have been found to target the GPCRs of the cochlea. Interestingly, many recent studies have demonstrated that GPCRs can participate in various pathogenic process related to hearing loss in the cochlea including heredity, noise, ototoxic drugs, cochlear structure, and so on. In this review, we comprehensively summarize the functions of 53 GPCRs known in the cochlea and their relationships with hearing loss, and highlight the recent advances of new techniques used in cochlear study including cryo-EM, AI, GPCR drug screening, gene therapy vectors, and CRISPR editing technology, as well as discuss in depth the future direction of novel GPCR-based drug development and gene therapy for cochlear hearing loss. Collectively, this review is to facilitate basic and (pre-) clinical research in this area, and provide beneficial help for emerging GPCR-based cochlear therapies.